Engineered ECM-like microenvironment with fibrous particles for guiding 3D-encapsulated hMSC behaviours1. Issue 13 (7th April 2015) - Shin, Young Min; Kim, Taek Gyoung; Park, Jong-Seok; Gwon, Hui-Jeong; Jeong, Sung In; Shin, Heungsoo; Kim, Kyung-Soo; Kim, Dongyoon; Yoon, Myung-Han; Lim, Youn-Mook
<x xml:space="preserve">Abstract</x> The incorporation of RGD-coupled fibrous particles into the alginate hydrogel promotes 3D-encapsulated cell behaviours by allowing mutual binding with the particles.